2005
DOI: 10.1007/s00198-005-1840-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher circulating hsCRP levels are associated with lower bone mineral density in healthy pre- and postmenopausal women: evidence for a link between systemic inflammation and osteoporosis

Abstract: Factors involved in inflammation are linked with those critical for bone remodeling. We examined the association between serum high sensitivity C-reactive protein (hsCRP) levels and bone mineral density (BMD) in healthy women. Serum concentrations of hsCRP and total alkaline phosphatase (ALP) were measured in premenopausal ( n =3,662) and postmenopausal ( n =1,031) women aged 30 years or older. BMD was measured at the femoral neck and lumbar spine using dual energy X-ray absorptiometry. According to the WHO de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
146
2
11

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(167 citation statements)
references
References 42 publications
8
146
2
11
Order By: Relevance
“…Our result that CRP plasma concentration was negatively correlated with relative bone mass and strength values is in contrast to a previous report 28 but is supported by the outcomes of a multitude of studies. 17,[29][30][31] Hence, negative correlations between CRP and relative bone variables, as found in this study, may represent an early indicator for the negative effect of chronic inflammation, which after prolonged exposure might result in decreased absolute bone mass and strength, as reported in other studies. 17,[29][30][31] In summary, we conclude that high body fat percentage was associated with lower relative bone mass and strength despite normal habitual muscle force in premenopausal women, indicating that high body fat percentage compromised the functional muscle-bone unit in these individuals.…”
Section: Discussionsupporting
confidence: 83%
“…Our result that CRP plasma concentration was negatively correlated with relative bone mass and strength values is in contrast to a previous report 28 but is supported by the outcomes of a multitude of studies. 17,[29][30][31] Hence, negative correlations between CRP and relative bone variables, as found in this study, may represent an early indicator for the negative effect of chronic inflammation, which after prolonged exposure might result in decreased absolute bone mass and strength, as reported in other studies. 17,[29][30][31] In summary, we conclude that high body fat percentage was associated with lower relative bone mass and strength despite normal habitual muscle force in premenopausal women, indicating that high body fat percentage compromised the functional muscle-bone unit in these individuals.…”
Section: Discussionsupporting
confidence: 83%
“…Visceral fat is not only specialized with regard to the storage and mobilization of lipids but also a remarkable endocrine organ that release proinflammatory cytokines stimulating bone resorption such as TNF alpha, interleukin 6, and Interleukin 18 [42][43][44]. Therefore, it is feasible that the resultant low-grade inflammation, which is known to be involved in the pathophysiologic mechanisms underlying osteoporosis [10], may lead to bone loss despite the protective effects of general obesity. In other studies, abdominal obesity was found to be a protective factor on BMD at the lumbar spine [5], the total hip [5,27], and the femoral neck [5].…”
Section: Discussionmentioning
confidence: 99%
“…The joint occurrence of the two diseases is thought to result from the common risk factors and path physiological mechanisms, such as smoking, a sedentary lifestyle, sex hormone deficiency, low-grade inflammation, and increased oxidative stress [8][9][10][11]. Cumulative evidence has demonstrated that increased bone loss and a lower bone mass are associated with cardiovascular mortality [12,13] and that an increased risk of cardiovascular events is proportional to osteoporosis severity at the time of diagnosis [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'étiologie multifactorielle de l'ostéoporose inclut effectivement une composante inflammatoire [16] et oxydative [17]. Parmi les molécu-les aux propriétés anti-oxydantes et anti-inflammatoires, on retrouve la vitamine E (50 à 70 % apportés par les huiles végétales et dans une moindre mesure, 12 %-18 %, par les végétaux) dont la capacité ostéo-protectrice a été décrite en particulier en situation d'apesanteur.…”
Section: Bénéfices Potentiels Sur Le Capital Osseuxunclassified